Changes in soil carbon inputs and outputs along a tropical altitudinal gradient of volcanic soils under intensive agriculture - Sierra, Jorge; Causeret, François (Geoderma, 2018)
Volcanic soils contain a large stock of soil organic carbon (SOC) which is highly vulnerable to changes in land use and climate warming. In this study we examine the changes of SOC stocks along a tropical elevation gradient (100 m–700 m; +437 mm yr−1 of rainfall and −0.7 °C every 100 m), which is subject to two intensive agricultural systems (banana monoculture and vegetable crops) characterised by the heavy use of fertilisers and pesticides. We hypothesise that in these systems SOC is mainly controlled by soil mineralogy, climatic factors and soil tillage. We used a process-based approach to determine soil C inputs and outputs along the elevation gradient. The banana monoculture systems (198 plots) are characterised by a temporal steady-state of SOC, and the vegetable crop systems (55 plots) present high annual SOC losses. The banana systems were used to determine for the first time the altitudinal change in the in situ rate constant of SOC mineralisation (kSOC). Under banana monoculture, SOC stock increased by 218%, C input from crop residues decreased by 44%, and kSOC decreased by 570% across the altitudinal gradient. These results indicated that the SOC gradient was mainly induced by changes in C outputs. Allophane content increased with altitude (R2 = 0.61; 8 g kg−1 every 100 m) and was positively correlated with SOC content (R2 = 0.51) and negatively correlated with kSOC (R2 = 0.53). We hypothesise that the physical protection of SOC within amorphous allophanic minerals was the main factor responsible for the kSOC and SOC stock gradients. Strictly, the effects of allophane content and rainfall cannot be separated because soil mineralogy in the studied area is mainly determined by the level of rainfall. Our process-based analysis indicated that changes in temperature along the elevation gradient could only explain 22% of the observed change in kSOC. SOC stocks under vegetable crops also increased with altitude; they were 57% lower than under banana at low altitude but only 9% lower at high altitude. This reflected simultaneously the higher C outputs under vegetable crops due to more intensive soil tillage, and the greater resilience to soil disturbance of protected SOC in altitude. The results suggested that neither soil nutrient content nor soil biological properties contributed to the SOC and kSOC gradients under the intensive cropping systems analysed during this study. Overall, we conclude that SOC might be more vulnerable to soil tillage and warming in low-altitude soils. •Soil organic carbon (SOC) increased by 220% from 100 m to 700 m of altitude.•SOC gradient was linked to the steep decrease of C outputs from mineralisation (kSOC).•Allophane content explained 53% of the variability of kSOC.•Decreasing temperature with altitude explained 22% of the kSOC gradient.•SOC in lowlands may be more vulnerable to changes in land use and warming.